Ketidaktepatan Kode Diagnosis Kasus Bedah RSU ‘Aisyiyah berdasarkan ICD-10 - Khumaira, Nurul Fitri; Wahyuni, Annisa; Siska, Siska (Politeknik Negeri Jember, 2024)
The high rate of coding inaccuracies can impact medical treatment cost claims, increase the workload of medical record staff, and lead to poor epidemiological disease data recording. This study aims to identify inaccuracies in inpatient surgical diagnosis coding based on ICD-10. The study uses a descriptive method. The population consists of all inpatient surgical medical records at RSU Aisyiyah Padang in 2023, with a sample size of 84 records selected using simple random sampling. Data analysis was performed descriptively using univariate analysis to determine the frequency distribution and the percentage of coding accuracy based on ICD-10. The study results show that 26.19% of diagnosis codes were inaccurate, while 73.81% were accurate. Coding inaccuracies were categorized into three groups: incorrect codes, fourth character errors, and third character errors. The Neoplasms category had the highest percentage of incorrect codes. The inaccuracies were mainly caused by a lack of attention to detail by coders and differences between the doctor's diagnostic terminology and the ICD-10. Solutions to reduce these errors include improving knowledge, effective communication with doctors, and adherence to coding guidelines.